The Relationship Between Personality and Employee Motivation in Organisation in Libya - Arzai, Saleh Khosa (2010)
This study is conducted to study the relationship between personality and employees' motivation in Libya. A survey method of data collection was used on one hundred and eighty employees of five SME'S in Libya. One hundred and forty two questionnaires were returned to which descriptive statistics was used to ascertain the personal information/demographic factors of the respondents. Pearson correlation was conducted on the independent variables (personality) and the dependent variable (motivation). The subsequent result shows some significant relationship between extroversion and need for achievement and need for power. Neuroticism is related to only need for affiliation and need for power, agreeableness is related to need for achievement and power, opennes is related to only need for affilliation and finally conciousness is related to only need for achivement. In the multiple regression, agreeableness made the largest contribution in explaining the need for achievement, openness made the largest contribution in explaining the need for affiliation and neuroticism contributed most in explaining the need for power and finally recommendations were also being discussed.